Head Injury with Retro-Ocular and Intracerebral Foreign Body in a Five-Year-Old Girl - Alvarez, Carlos (1996)
Here we introduce the case of a five-year-old girl, who felt down on a corn plant stake, resulting in head injury with prick-cutting injury, leaving some cane fragments along the stretch both retro-ocular and intracerebral. Both remision and recovery ad integrum thanks to surgical management, were obtained. The clinical case and evolution are discussed here.